Humour in mathematics teaching: A study in Portugal and Spain - Menezes, Luís (2022)
This study analyses humour in a school context in Portugal and Spain. The study aims to respond to the following questions: (1) Do mathematics teachers consider that they have a sense of humour? (2) What conception do they have of humour? (3) Do they consider humour to be compatible with the teaching of mathematics? and (4) If teachers use humour in the teaching of mathematics, how do they use it and for what purpose? To carry out this study, we adopted a mixed methodology. Mathematics teachers, Portuguese and Spanish, teaching from primary school level to higher education, were asked to respond to a questionnaire, comprising open and closed questions. Data analysis combines statistical with content analysis. The main results reveal that most teachers claim they appreciate/value humour and acknowledge its educational relevance. Most teachers claim they use it regularly and present examples of its use. These examples show small differences between Portuguese and Spanish teachers.